Efficacy of exercises in early-stage Parkinson’s disease (PARK-EASE trial): single-blind, randomised, controlled trial - Vinay Goyal; Sreenivas Vishnubhatla; Raktim Swarnakar; Sanjay Wadhwa; Srikumar Venkataraman (BMJ Neurology Open)
Objectives To assess the efficacy of exercises in early-stage Parkinson’s disease (PD).Design Single-blind, randomised controlled trial.Setting Tertiary rehabilitation care centre.Participants Forty individuals (≥18 years, either gender) with newly diagnosed PD (Hoehn and Yahr stage ≤2) on a stable dose of PD medications were randomised (1:1) to the intervention group (IG) and control group (CG).Interventions The IG received strengthening (30 min/day, 2 days/week), aerobic (30 min/day, 3 days/week) and agility (30 min/day, 2 days/week) exercises in a structured format for 12 weeks. CG received stretching exercises for 12 weeks.Main outcome measures Unified PD Rating Scale (UPDRS) III (motor) at week 12 (primary), UPDRS I (mentation, behaviour and mood), UPDRS II and VI (Schwab and England Activities of daily living Scale) and Parkinson’s Disease Quality of Life (PDQL) at week 12 (secondary).Results 36 participants completed 12-week study period. UPDRS III (lesser scores reflect improvement) at 12 weeks showed a significant between-group difference (−5.05 points (95% CI: −9.38 to −0.71), p=0.02). At 4 and 8 weeks, UPDRS III did not show a statistically significant between-group difference (−2.15 points (95% CI: −6.77 to 2.47) and −4.1 points (95% CI: −8.54 to 0.34), respectively). From baseline to 12 weeks, UPDRS III in the IG showed a 6.5-point (95% CI (4.85 to 8.14)) reduction, and the CG showed a 0.8-point increase (95% CI (−3.06 to 1.46)), PDQL (higher scores reflect improvement) in the IG showed a 8.45-point (95% CI (–12.78 to –4.11)) increase and CG showed a 2.75-point (95% CI (0.16 to 5.33)) reduction.Conclusions Structured exercises improve motor symptoms and quality of life in early-stage PD. Consistent adherence for at least 12 weeks is crucial for clinical improvement. Early initiation of exercises as neurorehabilitation is recommended. Further research on specific types, dosing and intensity of exercises with a larger sample size is warranted in early-stage PD.Trial registration number CTRI/2018/05/014241.